The Use of the Think Pair Share (TPS) Method as an Effort to Improve Students' Motivation and English Learning Outcomes - Sariayun Harahap (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2023)
This study aims to determine the impact of applying the Think Pair Share (TPS) method on learning English with Greetings and Leave Takings materials on increasing learning motivation and knowing the impact of applying the Think Pair Share (TPS) method on learning English with Greetings and Leave Takings materials on increasing student learning outcomes.The research method used is Classroom Action Research (CAR), which generally consists of 2 (two) cycles. Each cycle has 4 (four) stages namely planning, action, observation, and reflection.This research was conducted at X Adm Office SMK Negeri 1 Sipirok, totaling 32 people with a composition of 7 men and 25 women. The data collection techniques used were tests, observation sheets, and student questionnaires.From the results of the research on the cycle the teacher made improvements and students were reminded again about taking advantage of opportunities to discuss with their partners and how to work in good groups, where all members must play an active role in group discussions. After the improvement, there was an increase in learning outcomes in cycle II when compared to the previous cycle, which was originally only 16 students (50.00%) who had completed their studies, increased to 28 students (87.5%) who had completed their studies